Teaching primary mathematics - Turner, Sylvia (Los Angeles : SAGE, 2013)
An up-to-date and accessible textbook on teaching mathematics in primary schools, combining practical guidance for the classroom with key theoretical coverage. For those currently training to teach in primary education.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching (Elementary) -- Great Britain; Mathematics -- Study and teaching (Elementary).